1986
DOI: 10.1029/jc091ic02p02273
|View full text |Cite
|
Sign up to set email alerts
|

The necessity for a new parameterization of an empirical model for wind/ocean scatterometry

Abstract: This study reveals that the power‐law form of the Seasat A scatterometer system (SASS) empirical backscatter‐to‐wind model function (SASS 1), when combined with the sum‐of‐squares (SOS) wind retrieval algorithm, does not uniformly meet the instrument performance specification requirements. Analysis indicates that the horizontally polarized (Hpol) and vertically polarized (Vpol) components of the benchmark SASS 1/SOS wind retrieval system relating signal strength (backscatter) to wind speed yield self‐consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…In a recent paper, Woiceshyn et al [1986] have shown that the transfer (or model) functions used for horizontal incidenthorizontal scattered polarization (electric field vector perpendicular to the plane of incidence, abbreviated HH) are inconsistent with those used for vertical-vertical polarization (abbreviated V V). The differences in estimated wind speeds are quite large (up to 9 m s-• for high winds) and imply perhaps that the process of deducing the wind from the backscatter measurements was partially incorrect, that the model functions, avvø(•, Z, 0) and aHHø(•, Z, 0), when combined with the sum of squares (SOS) wind recovery algorithm [Jones et al, 1982;Pierson, 1984] were in error; or that a combination of both caused the discrepancies.…”
Section: Present Statusmentioning
confidence: 97%
“…In a recent paper, Woiceshyn et al [1986] have shown that the transfer (or model) functions used for horizontal incidenthorizontal scattered polarization (electric field vector perpendicular to the plane of incidence, abbreviated HH) are inconsistent with those used for vertical-vertical polarization (abbreviated V V). The differences in estimated wind speeds are quite large (up to 9 m s-• for high winds) and imply perhaps that the process of deducing the wind from the backscatter measurements was partially incorrect, that the model functions, avvø(•, Z, 0) and aHHø(•, Z, 0), when combined with the sum of squares (SOS) wind recovery algorithm [Jones et al, 1982;Pierson, 1984] were in error; or that a combination of both caused the discrepancies.…”
Section: Present Statusmentioning
confidence: 97%
“…The Seasat scatterometer wind-retrieval algorithm met system accuracy specifications in an overall sense; however, an error analysis by Woiceshyn et al (1986) reveals systematic biases at low and high winds. Wind-speed estimates apparently did not uniformly meet performance criteria.…”
Section: Introductionmentioning
confidence: 96%
“…Observational evidence for the long wave influence has been reported by Keller, et al, (1985Keller, et al, ( ,1989 Figure 2d). Wind Speed for Various Angles of Incidence, 9 ; b) Wind Direction (Jones, et al 1977); c) Long Wave Slope (Keller, et al, 1985); d) Atmospheric Stratification Unstable atmospheric stratification, as indicated by a negative air-sea temperature difference (Figure 2d), results in 1) a slightly higher near-surface (Lamb, 1932) which is an inverse function of water temperature; therefore, this mechanism has been proposed to explain observations which show an increase in the radar backscatter for increasing surface temperature, particularly at low wind speeds (Woiceshyn, et al, 1986;Donelan and Pierson, 1987;Kahma and Donelan, 1988 (Tsanis and Donelan, 1987 (October-December, 1985, the tower was outfitted with instruments to study wave spectra, wind (Huhnerfuss, 1983;Hughes and Gower, 1983), surface currents (Phillips, 1981), and the surface adjustment due to topographic interactions in shallow coastal areas (Valenzuela, 1985). (Geernaert, 1990).…”
mentioning
confidence: 99%
“…The determination that o°was in some way proportional to wind speed led to the proposal for a satellite-borne radar, by then known as a scatterometer, to obtain oceanic wind and wave information (Moore and Pierson, 1966 (Woiceshyn, et al, 1986 Reiterating the need for an improved, all-weather oceanic data base, the Navy proposed N-ROSS (Navy Remote Ocean Sensing System), a supposedly "scaled-down" version of NOSS, in April, 1981(Honhart, 1984 December, 1986(Graham, 1987Matthews; With these changes the scatterometer will become a far more attractive instrument in a programmatic sense (Brown and McCandless, 1988) (Rice, 1951;Barrick, 1968;Wright, 1966Wright, , 1968Valenzuela, 1968Valenzuela, , 1978Fung and Chan, 1969;Keller and Wright, 1975;Brown, 1978;Bahar, 1981;Durden and Vesecky, 1985;Plant, 1986;Holliday, 1986;Donelan and Pierso^i, 1987). To date, the three most common approaches to scattering problems are physical optics, small perturbation and two-scale composite surface methods^.…”
mentioning
confidence: 99%
See 1 more Smart Citation